Review of the genus Pityocona Meyrick, 1918 (Lepidoptera: Gelechiidae) in China, with descriptions of five new species - Chen, Mengting; Li, Houhun (Zootaxa, 2017)
The genus Pityocona is reviewed in China. Pityocona longovata sp. nov., P. transovata sp. nov., P. monoprocessa sp. nov., P. mastoidea sp. nov. and P. sinuosa sp. nov. are described as new; P. bifurcatus Wadhawan et Walia originally described from India is widely known in southern China as a pest of rice. Photos of adults and genitalia are provided, along with a key to all the Chinese species.